Innovative Education and Science in Information Technologies: Experience of N. Ye. Zhukovsky National Aerospace University (KhAI) - Kryvtsov, V.S.; Gorbenko А.V.; Kharchenko, V.S. (Science and Innovation, 2024)
Information technologies are among the most promising and fastest growing sectors in the world and in the Ukrainian industry. Herein, the authors share the experience of National Aerospace University (KhAI) in the personnel education and training for the IT industry and the results of successful cooperation with IT companies. Innovative education programs, as well as scientific and practical researches in the field of information technologies, which are implementing in KhAI have been discussed.